(untitled) (The Gaze: Journal of Tourism and Hospitality, 2016)
The article provides a review on the concepts of safety, security and surety in tourism and the repercussions that risk, vulnerability, crisis, disaster, hazard, emergency and political turbulence can pose upon the industry. The article aims not just to prioritize the impacts of disasters on tourism but also aims to focus upon the issues of crisis management, disaster management and new marketing approaches for revival of tourism which comparatively are the less touched upon issues in the context of Nepal. The concept of tourism decision making is also studied here in the light of various theories. The article also discusses on the cultural dimension of tourist decision making and crisis management in relation with national culture and some theoretical orientation of crisis management in relevance to tourism. The Gaze: Journal of Tourism and Hospitality Vol.7 2015 pp.1-36